A Corporate Mentoring Program Cross-Cultural Experience and the Impact on Self-Identity for Students From an Urban Community (Journal of Education and Development, 2023)
Cross-cultural mentoring can lead to personal development through experiencing cultural differences that cultivate individual virtues and values. Culture is an aspect of self-identity. Self-identity for adolescents is important for their long-term development. This study examines a corporate mentoring program that offers a cross-cultural experience for participants. It aimed to determine if the mentoring program influenced participants’ self-identity and if there was a correlation between culture and their self-identity. The study was guided by identity control theory. A 10-question Likert scale survey was administered to the 20 urban high school students at the completion of their mentoring program for the academic year, which included nine sessions. The study found that the corporate mentoring program did impact the self-identity of urban youth; however, there was no correlation between the cross-cultural experience and their self-identity. This finding adds to the research on youth identity formation. Further research is needed on how different cultural influences may contribute to youth identity formation.